1999
DOI: 10.1159/000017405
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Cortical Dysplasia: Giant Neurons Show Potential for Increased Excitation and Axonal Plasticity

Abstract: Cerebral cortical dysplasia (CD) is a common cause of intractable childhood epilepsy. Five cases of CD were analyzed for GABAA receptor subunit β (GABA), glutamate decarboxylase, AMPA receptor subunit 1 (GluR1) and subunit 2/3 (GluR2/3), and NMDA receptor 2 (NMDAR2) immunoreactivity. Antisera to the highly polysialylated neural cell adhesion molecule (PSA-NCAM) and human unc-33-like phosphoprotein 1 (hUlip 1) were used to identify neurons with ‘developmentally immature’ characteristics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 41 publications
3
30
0
1
Order By: Relevance
“…For example, qualitative immunocytochemical studies using indirect markers of GABAergic neurons (e.g., calretinin, calbindin and parvalbumin) or mRNA levels of GABA A receptor subunits from CD tissue have reported decreased numbers of inhibitory neurons or differential expression of GABA A receptor subunits, suggesting the potential of reduced inhibition [Crino et al, 2001;Spreafico et al, 1998Spreafico et al, , 2000Thom et al, 2003]. Other studies have reported changes in glutamate receptor subunit protein and mRNA expression in CD tissue, supporting the concept that AMPA and NMDA excitatory functions may be enhanced [Crino et al, 2001;Kerfoot et al, 1999;Najm et al, 2000;Ying et al, 1998]. Our synaptic frequency data from normalpyramidal and cytomegalic neurons initiate the process of understanding alterations in glutamate and GABAergic synaptic properties in pediatric CD.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…For example, qualitative immunocytochemical studies using indirect markers of GABAergic neurons (e.g., calretinin, calbindin and parvalbumin) or mRNA levels of GABA A receptor subunits from CD tissue have reported decreased numbers of inhibitory neurons or differential expression of GABA A receptor subunits, suggesting the potential of reduced inhibition [Crino et al, 2001;Spreafico et al, 1998Spreafico et al, , 2000Thom et al, 2003]. Other studies have reported changes in glutamate receptor subunit protein and mRNA expression in CD tissue, supporting the concept that AMPA and NMDA excitatory functions may be enhanced [Crino et al, 2001;Kerfoot et al, 1999;Najm et al, 2000;Ying et al, 1998]. Our synaptic frequency data from normalpyramidal and cytomegalic neurons initiate the process of understanding alterations in glutamate and GABAergic synaptic properties in pediatric CD.…”
Section: Discussionmentioning
confidence: 88%
“…This hypothesis is supported by circumstantial anatomic and correlative electrocorticography (ECoG) studies demonstrating an association between the presence of dysmorphic cells with interictal and ictal abnormalities in CD patients [Boonyapisit et al, 2003;Palmini, 2000;Rosenow et al, 1998;Spreafico et al, 1998;Tassi et al, 2001]. Similarly, in CD tissue investigators have noted a qualitative reduction in GABAergic neurons and changes in the coassembly of AMPA, NMDA and GABA A receptor subunits in and around human dysplastic lesions, suggesting the possibility of enhanced excitation and partial loss of inhibition leading to seizures [Crino et al, 2001;Kerfoot et al, 1999;Mikuni et al, 1999;Najm et al, 2000;Ying et al, 1998]. …”
Section: Introductionmentioning
confidence: 93%
“…Ying et al [63] have found that hyperexcitability of dysplastic regions may result, in part, from the presence of NMDAR2 subunits and selectively expressed NMDAR1 splice variants in dysplastic neurons (see also the article by Kerfoot et al [64]). Direct electrophysiologic recordings from 'dysmorphic/bizarre' neuroglial cells in corticectomy specimens will also be valuable in assessing their potential contribution to seizure genesis.…”
Section: And Cortical Tubers As Seizure-generating Lesionsmentioning
confidence: 99%
“…Comparable findings have been described in cortical tissue resected from patients diagnosed with intractable epilepsy secondary to cortical dysplasia (Ferrer et al, 1992; AlonsoNanclares et al, 2004). Cytomegalic neurons and large cells with atypical morphology have been suggested to play an important role in the generation of epileptic activity due to their abnormal electrophysiological properties (Kerfoot et al, 1999;Cepeda et al, 2003). …”
mentioning
confidence: 99%